Seeing through the hot air balloon a study on communication and hierarchical relationships in Greenwich main office - Reyes, Rowena Uson (2007.)
"Communication and relationships among high-level managers, supervisors and subordinates in Greenwich main office were specifically evaluate in the study. Greenwich is the country's leading pizza chain with about 190 main office workforce supporting over 200 branches nationwide. The state of communication and hierarchical relationships within the main office was studied using the perspectives of subordinates. The subordinates are non-managerial employees belonging to rank and file, technical specialist and officer positions. A total of 100 respondents accomplished the survey questionnaire and 10 for focus interview. Drawing from organizational systems theories (primarily Rensis Likert's four systems) as well as interpersonal communication principles, the study findings indicate that participative-democratic system permeates Greenwich main office. Communication in Greenwich main office generally moves in downward, upward and horizontal directions. The flow of information is initiated by high-level managers, supervisord and subordinates. Directives are repeatedly communicated and mostly through memo. Other types of information like suggestions, complaints, feedback, commendations and personal problems are sometimes conveyed. Performance appraisal or assessment of employee's performance is also an important means of communication concerns to supervisors and subordinates. Furthermore, findings indicate that there is more willingness among subordinates to discuss matters directly related to their jobs than to communicate suggestions and issues they have with their supervisors. The timeliness or speed at which information is received seems inefficient considering that avenues for communication sufficiently exists in the main office. Organizational goals appear to be clearly conveyed and the information obtained from the management is generally regarded as credible and reliable. Subordinates correspond with the plans of the management for the organization and perceive as effectively implemented. However, subordinates may need to further realize that their viewpoints are heard and considered. There is motivation among subordinates to work efficiently and feedback helps them know how to improve their performance. On the other hand, supervisors may need to develop their capacity of dealing properly with poor performance to help enrich supervisor-subordinate relationships."
Thesis (M.A. Communication Research)--University of the Philippines, Diliman.
Keywords: Communication in management -- Philippines; Communication in personnel management -- Philippines